THE INCREASING INCOME STRATEGY OF SUMBER AGUNG VILLAGE WEST PESIR DISTRICT THAT IMPACT ON COMMUNITY ECONOMY FROM THE PERSPECTIVE OF SIYASAH MALIYAH: STRATEGI PENINGKATAN PENDAPATAN PEKON SUMBER AGUNG KABUPATEN PESISIR BARAT YANG BERDAMPAK KEPADA EKONOMI MASYARAKAT DALAM PERSPEKTIF SIYASAH MALIYAH - Apriyan, Elma; Santoso, Rudi; Fauzi, Mohammad Yasir; Zaharah, Rita (Constitutional Law Society, 2024)
The enactment of Law Number 6 of 2014 concerning Villages and Law Number 23 of 2014 concerning Regional Government gives villages the right to regulate their regional affairs. In increasing the village's original income, the village government has the right and authority to widely utilize village wealth. Regarding village income sources, efforts to mobilize resources to develop the people's economic potential will increase people's productivity, so that the productivity of both human resources and natural resources around the people can be increased. In this research study, the formulation of the problem is how the strategy for increasing village original income has an impact on the community's economy and how siyāsah māliyah reviews this strategy. The aim of this research are to find out how the strategy of increasing village original income has an impact on the community's economy and how siyāsah māliyah views this strategy. The type of research used in this research is field research, where this research was carried out by interviewing staff at Sumber Agung Pekon, Ngambur District, Pesisir Barat Regency. Data analysis was carried out qualitatively, processing data analysis using descriptive analysis methods, namely discussions based on general thought patterns and then concluded in specific terms. The research results show that the strategy to increase village original income which has an impact on the community economy in the Sumber Agung area, Ngambur District, Pesisir Barat Regency is by establishing village-owned business entities, developing beach tourism, and also having village markets. The conclusion from the results of this research is that the strategy to increase village original income which has an impact on the economy of the community in the Ngambur area has made a contribution, although not much. Siyāsah māliyah's review of the increase in original village income which has an impact on the economy of the community in the Sumber Agung District of Ngambur is in accordance with the principle of benefit, namely prioritizing the interests of the people rather than the interests of the individual.